Método Pilates: equilíbrio perfeito entre corpo e mente? - Lot, Letícia [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Taking as base the Brazilian Physical Education History, it’s possible to observe how much the recognizable corporal activity as smooth and alternative, giving origin to non traditional ways to move the body that receives the name of “alternative corporal practices” has increased lately. Therefore this research was done with objective to raise interest and stimulate physical educational professional and general interested people knowledge to the work of a corporal approach called “Pilates Method”. Based on a bibliographic research in sites, articles, and books about Pilates method, alternative corporal practices and physical education history, we tried to gather, in one material, important information about Pilates method. To organize the material here shown, we guided ourselves on the collection of UNESP´s library and on Pilates methods training courses about which were made references in the body text and were mentioned the bibliographic reference for further profound study of interested people. We hope that Physical Educational professionals and further interested people find in this conclusion course work that intends to contribute to the method divulgation assistance for higher and deeper knowledge concerning to the origin, principles and possibilities of practical appliance pedagogy of Pilates Methods.

Tomando como base a história da Educação Física no Brasil, é possível observarmos o quanto as atividades corporais reconhecidas como suaves e alternativas, dando origem à formas não tradicionais de se movimentar o corpo e que recebem o nome de “Práticas Corporais Alternativas”, tem aumentado nos últimos anos. Em função disso, esta pesquisa foi realizada com o objetivo de despertar o interesse e estimular o conhecimento dos profissionais de Educação Física e interessados em geral, para o trabalho de abordagem corporal denominado Método Pilates. Com base em pesquisa bibliográfica em sites, artigos e livros que tratam do Método Pilates, das Praticas Corporais Alternativas e da História da Educação Física, procuramos reunir, num único material, informações importantes sobre o Método Pilates. Para a organização do material ora apresentado, nos pautamos em livros encontrados no acervo da biblioteca da UNESP e utilizados em cursos de formação do Método Pilates, dos quais foram citados no corpo do texto e mencionados como referências bibliográficas, para maior aprofundamento dos interessados. Esperamos que os profissionais de Educação Física e demais interessados encontrem neste Trabalho de Conclusão de Curso, que visa contribuir com a popularização desse método, subsídios para um maior conhecimento e aprofundamento acerca da origem, dos princípios e das possibilidades de aplicação prática pedagógica do Método Pilates.
Keywords: Educação fisica; Pilates, Joseph H. (Joseph Hubertus); Prática corporal alternativa; Método Pilates; Pilates Methods